Cross-species Utility of 22 Microsatellite Markers in the Melodious Warbler (Hippolais Polyglotta). (May 2014) - Engler, Jan O.; Secondi, Jean; Dawson, Deborah A.; Roderus, David; Elle, Ortwin; Hochkirch, Axel
Microsatellites are a valuable tool in the analysis of population genetic structure. Utilising microsatellite markers that were originally isolated from other species (cross-species amplification) can prove an efficient way, in terms of time and cost, to obtain markers for genetic studies. Here, 55 avian microsatellite primer pairs were tested for the cross-amplification in the Melodious Warbler ( Hippolais polyglotta ). Thirty-five markers amplified, of which 22 were polymorphic, displaying two to nine alleles in the 15 individuals genotyped. The 35 markers which amplified in the Melodious Warbler were tested in its sister species the Icterine Warbler ( H. icterina ). Twenty-four markers were amplified, 14 of which were polymorphic in the five H. icterina individuals genotyped. Thirteen loci were polymorphic in both species. The polymorphic loci identified are suitable for analysing the genetic population structure and assigning parentage.